Consideration of Individual Differentiations of People Obligated by Law and Its Effect in Variation of Ijtihād Tanzili - Kattoua, Mohamad Turky (Journal of Islamic and Religious Studies, 2018)
The downloading of the legal rulings on the facts and their transfer from abstraction to application needs a deep philosophical look from Mujtahid and Mufti. Among the things that must be taken into account consider individual differences between taxpayers because these differences may require a change in the Shari'a ruling by the change of the person who owns the incident according to its characteristics and conditions, from the clues that it embraces and requires this change. This indicates that individual differences between taxpayers should be taken into account during tinnitus litigation which is seen as a pilgrimage to the origins of the Sharia and its general rules and its effects were manifested and manifested in the methods and methods of fundamentalists and jurists.